2020
DOI: 10.1186/s13027-020-00286-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of human papillomavirus infection in the etiology of vulvar cancer in Italian women

Abstract: Background: Vulvar squamous cell carcinoma (VSCC) is a rare malignancy of the female genital tract. We aimed to determine the mucosal high-risk human papillomavirus (HPV)-attributable fraction of VSCCs from Italian women using multiple markers of viral infections. Methods: VSCCs and 8 metastatic lymph node samples from 107 Italian women were analyzed by a highly typespecific multiplex genotyping assay for the presence of DNA from 119 different HPVs. Tissues were further analyzed for HPV RNA and for upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 51 publications
2
57
0
1
Order By: Relevance
“…Persistent infection with high-risk HPVs, most commonly HPV16 and HPV18, is the main risk factor for development of almost all cases of cervical cancer (Doorbar, 2006;Schiffman et al, 2016), and of significant fraction of penile and anal cancers (Moscicki and Palefsky, 2011), vulvar cancer (Preti et al, 2020), as well as tumors of the upper respiratory tract, including head and neck cancers (Bzhalava et al, 2020). Most HPV infections of the cervix are successfully cleared by the host immune system in 2-3 years, but in several cases the infection may persist over the time leading to CIN graded 1 to 3 that eventually evolve during a long lasting period in invasive cervical carcinoma (McCredie et al, 2008;Doorbar et al, 2012;Oyervides-Munoz et al, 2018).…”
Section: Hpv Infection and Viral Gene Expressionmentioning
confidence: 99%
“…Persistent infection with high-risk HPVs, most commonly HPV16 and HPV18, is the main risk factor for development of almost all cases of cervical cancer (Doorbar, 2006;Schiffman et al, 2016), and of significant fraction of penile and anal cancers (Moscicki and Palefsky, 2011), vulvar cancer (Preti et al, 2020), as well as tumors of the upper respiratory tract, including head and neck cancers (Bzhalava et al, 2020). Most HPV infections of the cervix are successfully cleared by the host immune system in 2-3 years, but in several cases the infection may persist over the time leading to CIN graded 1 to 3 that eventually evolve during a long lasting period in invasive cervical carcinoma (McCredie et al, 2008;Doorbar et al, 2012;Oyervides-Munoz et al, 2018).…”
Section: Hpv Infection and Viral Gene Expressionmentioning
confidence: 99%
“…The incidences of human papillomavirus (HPV) driven cancers, including cervical, vulvar, penile, anal, and head and neck cancers continue to increase despite the availability of a prophylactic vaccine targeted at preventing initial infection [ 1 , 2 , 3 , 4 ]. This is especially true in countries with limited resources and in need for preventative screening measures.…”
Section: Introductionmentioning
confidence: 99%
“…Basic method for cervical cancer screening is Pap smear which combined with HPV test in most of the times [9]. Mario Preti, et al study on VSCC cases identified HPV as the causative object for vulvar carcinogenesis [10], as currently there are no recommended screening strategies for vulvar cancer, HPV immunization through vaccination may be the only effective way for prevention [11].…”
Section: Key Clinical Pointsmentioning
confidence: 99%